2-Hydroxyglutaric aciduria as a cause for seizure-like episodes in a domestic shorthair cat. Issue 1 (June 2019) - Nye, George J; Major, Alison C; Liebel, Francois X
Case summary: A 14-month-old male castrated domestic shorthair cat, which 2 months prior to presentation underwent hindlimb amputation following a road traffic accident, presented for investigation of four suspected generalised tonic–clonic seizures. Neurological examination was unremarkable. Routine blood work (haematology, biochemistry, ammonia, preprandial bile acids) was unremarkable. MRI of the brain identified marked symmetrical T2-weighted hyperintensities of the cerebellum and brainstem, mainly affecting the grey matter. Urine amino acid and mucopolysaccharide levels were unremarkable. Urine organic acids on two separate samples, 35 days apart, identified highly increased excretion of 2-hydroxyglutaric acid, indicative of 2-hydroxyglutaric aciduria. The cat was started on anticonvulsant therapy with phenobarbitone, which, at the point of writing, has improved seizure control, although the cat has not achieved seizure freedom. Relevance and novel information: This case report describes the first reported case of a 2-hydroxyglutaric aciduria, an inherited neurometabolic disorder, as a cause for seizure-like episodes in a cat.